2022
DOI: 10.1107/s2053230x22008317
|View full text |Cite
|
Sign up to set email alerts
|

Structure of angiogenin dimer bound to double-stranded RNA

Abstract: Angiogenin is an unusual member of the RNase A family and is of great interest in multiple pathological contexts. Although it has been assigned various regulatory roles, its core catalytic function is that of an RNA endonuclease. However, its catalytic efficiency is comparatively low and this has been linked to a unique C-terminal helix which partially blocks its RNA-binding site. Assuming that binding to its RNA substrate could trigger a conformational rearrangement, much speculation has arisen on the topic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
1
0
1
Order By: Relevance
“…However, since the conservation of the structural and functional properties of ANG can be dramatically modified by even slight modifications related to particular mutations [ 165 ], the different propensity to form dimers might somehow modify the functional properties of the enzyme in vivo, thereby affecting either ANG nuclear translocation or enzymatic efficacy. Incidentally, it has been recently reported that ANG can form a non-swapped dimer upon associating with a ds-RNA duplex, although this event has been registered only in vitro [ 196 ]. Nevertheless, the structural arrangements consequent to the interaction of ANG with RNAs, and the possible formation of dimeric or oligomeric derivatives could somehow affect the properties of the native enzyme.…”
Section: Possible Physio-pathological Effects Of Ang Self-associationmentioning
confidence: 99%
“…However, since the conservation of the structural and functional properties of ANG can be dramatically modified by even slight modifications related to particular mutations [ 165 ], the different propensity to form dimers might somehow modify the functional properties of the enzyme in vivo, thereby affecting either ANG nuclear translocation or enzymatic efficacy. Incidentally, it has been recently reported that ANG can form a non-swapped dimer upon associating with a ds-RNA duplex, although this event has been registered only in vitro [ 196 ]. Nevertheless, the structural arrangements consequent to the interaction of ANG with RNAs, and the possible formation of dimeric or oligomeric derivatives could somehow affect the properties of the native enzyme.…”
Section: Possible Physio-pathological Effects Of Ang Self-associationmentioning
confidence: 99%
“…Οι αλληλεπιδράσεις της hAng είναι πολλαπλές και κρίσιμες για την in vivo λειτουργία της, ενώ μόλις που αρχίζουν να γίνονται κατανοητές. Παρόλο που αυτό το σύμπλοκο hAng-RNA δε συμβαίνει in vivo, οι παρατηρούμενες αλληλεπιδράσεις της hAng με το RNA, μπορούν να βοηθήσουν να εξαχθούν τα πρώτα δομικά μοντέλα, πιο σχετικών αλληλεπιδράσεων της hAng, με γνωστούς in vivo στόχους (Sievers & Ficner, 2022).…”
Section: εικόνα 5: σύγκριση των δομών της Hang (αριστερά) και της Rna...unclassified